1994
DOI: 10.1079/bjn19940173
|View full text |Cite
|
Sign up to set email alerts
|

Effect of food intake on energy and protein metabolism in the skin of Romney sheep

Abstract: Sheep fed on either a low (500 g lucerne (Medicago sativa) chaff/d; L) or high (1 100 g lucerne chaffld; H) intake had measurements made, using arterio-venous techniques, of blood flow and energy metabolite and cysteine utilization in the skin. Sheep on the H intake had significantly increased skin blood flow (P = 0.014) and oxygen uptake (P = 0.05). Although the H sheep had higher skin blood flow they showed no difference in skin uptake of either glucose or acetate compared with the L sheep, but the €5 sheep … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 16 publications
(37 reference statements)
1
4
1
Order By: Relevance
“…Our results on restricted lambs did not validate the positive relationship between the weights of reticulo-rumen, intestine and liver on the one hand, and intake on the other hand, clearly established elsewhere in underfed growing animals (Ferrell et al, 1986;Drouillard et al, 1991;Kabbali et al, 1992) and in adults (Nozière et al, 1999;Atti et al, 2000). Conversely, the weight of skin was higher for sheep in H group than for restricted ones (L and M), since skin is a metabolic organ (Harris et al, 1994). There was a close relationship between level of feeding and the weight of some non-carcass components, namely metabolic organs (Koong et al, 1982;Drouillard et al, 1991).…”
Section: Discussioncontrasting
confidence: 93%
“…Our results on restricted lambs did not validate the positive relationship between the weights of reticulo-rumen, intestine and liver on the one hand, and intake on the other hand, clearly established elsewhere in underfed growing animals (Ferrell et al, 1986;Drouillard et al, 1991;Kabbali et al, 1992) and in adults (Nozière et al, 1999;Atti et al, 2000). Conversely, the weight of skin was higher for sheep in H group than for restricted ones (L and M), since skin is a metabolic organ (Harris et al, 1994). There was a close relationship between level of feeding and the weight of some non-carcass components, namely metabolic organs (Koong et al, 1982;Drouillard et al, 1991).…”
Section: Discussioncontrasting
confidence: 93%
“…However, the difference between the two groups (0.08, or 8%) is not as large as the difference in diet might have suggested. This is in accordance with the conclusions of Harris et al 19. These authors fed sheep a low or high intake and showed that although blood flow, protein synthesis and energy supply increased by 200–300% in the skin of sheep fed a high intake, wool production only increased by 10–20%, suggesting that nutrient flux changes are not the only level of regulation of wool production.…”
Section: Discussionsupporting
confidence: 91%
“…The present experiment was designed to test the effect of age and level of food intake on the kinetics of incorporation of the dietary carbon signal in wool from sheep raised under controlled laboratory conditions. Wool growth is markedly influenced by plane of nutrition and the major limiting nutrients are essential amino acids, and in particular sulfur‐containing amino acids 17–19. The effect of age on the growth of wool remains unclear.…”
mentioning
confidence: 99%
“…A lower intake results in a slight decrease in the fractional protein synthesis rate in the digestive tract, which could explain in part weight changes, whereas fractional synthesis rate does not vary in the liver [73] [60].…”
Section: Introductionmentioning
confidence: 99%